Barriers and facilitators for implementation of electronic consultations (eConsult) to enhance access to specialist care: a scoping review. Issue 5 (13th September 2019) - Osman, Mohamed A; Schick-Makaroff, Kara; Thompson, Stephanie; Bialy, Liza; Featherstone, Robin; Kurzawa, Julia; Zaidi, Deenaz; Okpechi, Ikechi; Habib, Syed; Shojai, Soroush; Jindal, Kailash; Braam, Branko; et al.
Abstract : Introduction: Electronic consultation (eConsult)—provider-to-provider electronic asynchronous exchanges of patient health information at a distance—is emerging as a potential tool to improve the interface between primary care providers and specialists. Despite growing evidence that eConsult has clinical benefits, it is not widely adopted. We investigated factors influencing the adoption and implementation of eConsult services. Methods: We applied established methods to guide the review, and the recently published Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews to report our findings. We searched five electronic databases and the grey literature for relevant studies. Two reviewers independently screened titles and full texts to identify studies that reported barriers to and/or facilitators of eConsult (asynchronous (store-and-forward) use of telemedicine to exchange patient health information between two providers (primary and secondary) at a distance using secure infrastructure). We extracted data on study characteristics and key barriers and facilitators were analysed thematically and classified using the Quadruple Aim framework taxonomy. No date or language restrictions were applied. Results: Among the 2579 publications retrieved, 130 studies met eligibility for the review. We identified and summarised key barriers to and facilitators of eConsult adoption and implementation across four domains: provider, patient, healthcare system and cost. Key barriers were increased workload for providers, privacy concerns and insufficient reimbursement for providers. Main facilitators were remote residence location, timely responses from specialists, utilisation of referral coordinators, addressing medicolegal concerns and incentives for providers to use eConsult. Conclusion: There are multiple barriers to and facilitators of eConsult adoption across the domains of Quadruple Aim framework. Our findings will inform the development of practice tools to support the wider adoption and scalability of eConsult implementation.